Bone mineral density in subjects with mild asthma randomised to treatment with inhaled corticosteroids or non-corticosteroid treatment for two years. Issue 4 (1st April 2001) - Tattersfield, A E; Town, G I; Johnell, O; Picado, C; Aubier, M; Braillon, P; Karlström, R
Abstract : BACKGROUND: Inhaled corticosteroids are clearly beneficial for patients with asthma of moderate severity, but the risks and benefits of using them in patients with milder asthma are less clear. We have compared the change in bone mineral density over 2 years in adults with mild asthma randomised to receive an inhaled corticosteroid or non-corticosteroid treatment. METHODS: Subjects with mild asthma (mean forced expiratory volume in one second (FEV1 ) 86% predicted, mean age 35 years, taking β agonists only) were randomised to receive inhaled budesonide, inhaled beclomethasone dipropionate, or non-corticosteroid treatment for 2 years in a prospective randomised open study in 19 centres in France, New Zealand, Spain, and the UK. The corticosteroid dose was adjusted according to a written self-management plan. The main outcome measure—change in bone mineral density after 6, 12, and 24 months—was measured "blind". Secondary outcomes included lung function, the relation between change in bone density and inhaled steroid dose and change in biochemical markers of bone metabolism. RESULTS: Of 374 subjects randomised, 239 (64%) completed the study and were included in the analysis. The median daily doses of inhaled budesonide (n=87) and beclomethasone (n=74) were 389 μg and 499 μg, respectively. Subjects treated with an inhaled corticosteroid had better asthma control than those in the reference group (n=78). Change in bone mineral density did not differ between the three groups over the 2 years, nor did it correlate with changes in markers of bone metabolism. The mean change in bone mineral density over 2 years in the budesonide, beclomethasone dipropionate, and reference groups was 0.1%, –0.4%, and 0.4% for the lumbar spine and –0.9%, –0.9%, and –0.4% for neck of the femur. Mean daily dose of inhaled steroid was related to reduction in bone mineral density at the lumbar spine but not at the femoral neck. CONCLUSION: In subjects with mild asthma an inhaled corticosteroid provided better asthma control than alternative non-corticosteroid treatment with no difference in change in bone mineral density over 2 years. The relation between dose of inhaled corticosteroid and change in bone density at the lumbar spine may be due to a direct effect of inhaled corticosteroids on bone. Since inhaled steroid dose is also related inversely to lung function, an effect of asthma severity on bone density was also possible.